Mountain of ice [videorecording (DVD)] - Clark, Liesl; Schreiber, Liev (WGBH Boston Video, 2006)
Mountaineers and scientists explore Antarctica and climb the continent's highest peak, the Vinson Massif. The present-day expedition is interwoven with a look back at the race between Scott and Amundsen to reach the South Pole in 1912.